RESPONS ENAM VARIETAS PADI Sawah (Oryza sativa, L.) PADA PERBEDAAN UMUR BIBIT DI LAHAN RAWA (Responses of Six Paddy varieties at Different Age Seedling at Peatland.) - Tiur Hermawati (Bioplantae, 2012)
This research was conducted to observe the effect of age’s differenceseedling to growth and yield of six Paddy varieties at peatland. Theexperiment was arranged in factorial Randomized Block Design withthree replications. The first factors were time of age seedling (3, 4, 5, 6weeks), and the second factors were six cultivars of paddy (Cisokan, IR-42, IR-64, Batanghari, and two local cultivars, there are Ceko danKuatik). The data were analyzed with ANOVA and DMRT. The resultsshowed that, there no interaction effect between seedling age andcultivars. Furthermore, there is no simple effect, on relative growth rate(RGR) and maximum advantity shoots, but signifianly influence toheight of plant and Net Assimilation Rate (NAR), rate of initation andyield. Cisokan and Batanghari cultivars were showed the highest yieldKey words : Paddy, varieties, NAR, PGR